2002
DOI: 10.1086/341627
|View full text |Cite
|
Sign up to set email alerts
|

Acetic Acid in the Hot Cores of Sagitarrius B2(N) and W51

Abstract: We have detected interstellar acetic acid (CH 3 COOH) toward the hot core source W51e2. This is the first new source of interstellar CH 3 COOH since its discovery by Mehringer et al. toward the hot core source Sgr B2(N-LMH). In this paper, we report CH 3 COOH observations at two new frequencies toward Sgr B2(N-LMH) with the OVRO array and at 10 frequencies toward W51e2 with the Berkeley-Illinois-Maryland Association array. Toward Sgr B2(N-LMH) the agreement in positions, intensities, and velocities between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 36 publications
5
83
0
Order By: Relevance
“…Acetic acid has been observed to be between 1/10 to 1/100 less abundant than methyl formate (Mehringer et al 1997;Remijan et al 2002Remijan et al , 2003Cazaux et al 2003), whereas the abundance of ethanol has been found to be between 0.3 and 3 times that of dimethyl ether (Millar et al 1988;Ikeda et al 2001;Nummelin et al 1998a;White et al 2003). The contradiction with the MEP comes from the relative stabilities of these isomers.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Acetic acid has been observed to be between 1/10 to 1/100 less abundant than methyl formate (Mehringer et al 1997;Remijan et al 2002Remijan et al , 2003Cazaux et al 2003), whereas the abundance of ethanol has been found to be between 0.3 and 3 times that of dimethyl ether (Millar et al 1988;Ikeda et al 2001;Nummelin et al 1998a;White et al 2003). The contradiction with the MEP comes from the relative stabilities of these isomers.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The chemistry of the W51e2 region has been investigated by several groups. For example, Zhang et al (1998) has done CH 3 CN and CS (3-2) observations, Remijan et al (2004Remijan et al ( , 2002 investigated CH 3 CN and CH 3 COOH, Liu et al (2001) looked for HCOOH in this source and Kuan et al (2004) searched for several molecules of potential prebiotic importance. The hydrogen column density 3.6 × 10 23 cm −2 (Ikeda et al 2001) is based on C 18 O data from Schloerb et al (1987).…”
Section: Source Selectionmentioning
confidence: 99%
“…We present observations searching for PN and PO toward two massive starforming regions: the W51 e1/e2 and the W3(OH) complexes (with luminosities of 1.5 × 10 6 and 1.0 × 10 5 L e , respectively). The W51 star-forming region, located at a distance of 5.1 kpc (Xu et al 2009) in the Sagittarius arm of our Galaxy, harbors two compact radio sources (Scott 1978) known as e1 and e2, which are associated with hot molecular cores with a rich chemistry (Zhang & Ho 1997;Zhang et al 1998;Ikeda et al 2001;Liu et al 2001;Remijan et al 2002;Demyk et al 2008;Kalenskii & Johansson 2010;Lykke et al 2015). The W3(OH) complex, located at 2.04 kpc (Hachisuka et al 2006), harbors two massive objects separated by 6″: the UC H II region W3(OH) (Wilner et al 1995) and the chemically rich W3(H 2 O) hot molecular core (Wyrowski et al 1999;Zapata et al 2011;Qin et al 2015).…”
Section: Introductionmentioning
confidence: 99%